Unpacking Performance and Empowerment in Female Farmers' Groups : The Case of the Fadama Project in Nigeria - Porter, Raewyn; Zovighian, Diane (World Bank, Washington, DC, 2015)
Women play an important role in rural economic activity but face severe constraints to productivity and socioeconomic security. Nigeria's agriculture sector employs 35 percent of women and up to 44 percent of female heads of households. Yet a number of factors constrain the expansion and diversification of agricultural activities, including fewer rights to land than men, lower access to credit, and inequitable access to inputs, fertilizers, and extension services. As a result, their agricultural productivity remains lower than that of men and their vulnerability to food insecurity and poverty higher. How to help female farmers increase their agricultural productivity and expand their economic opportunities is thus a key policy question. The government sees its agriculture transformation agenda (ATA) as a critical tool for driving rural income growth, accelerating the achievement of food and nutritional security, generating employment, and transforming the country into a leading player in global food markets. The strategy is to improve the value chains of a number of agricultural commodities by focusing on key aspects, including the availability and provision of improved inputs (seed and fertilizer), support for increased productivity and production, and the establishment of staple crop processing zones. With a view to informing the design of future agriculture policies and projects, this research investigated the experience of female farmers in an existing agriculture development project, the National Fadama Development Project (Fadama). Fadama is a community-driven development (CDD) project that aims to reduce rural poverty and increase food availability throughout all 36 states and the Federal capital territory in Nigeria. In particular, the research examines: target; performance; and empowerment of female farmers. This paper focuses predominantly on female Fadama user groups (FUGs) involved in cassava and palm oil processing, as these are the main crops with which women work under Fadama in Ogun state. Section A presents the factors that facilitate and shape women s access to and performance in FUGs. Section B discusses how women s increased income under the project affects their economic empowerment. Section C draws conclusions on the basis of this research, laying out key findings and exploring their operational and policy implications.